Arabidopsis Iron Superoxide Dismutase FSD1 Protects Against Methyl Viologen-Induced Oxidative Stress in a Copper-Dependent Manner - Melicher, Pavol; Dvořák, Petr; Krasylenko, Yuliya; Shapiguzov, Alexey; Kangasjärvi, Jaakko; Šamaj, Jozef; Takáč, Tomáš (Frontiers in Plant Science, 2022)
Iron superoxide dismutase 1 (FSD1) was recently characterized as a plastidial, cytoplasmic, and nuclear enzyme with osmoprotective and antioxidant functions. However, the current knowledge on its role in oxidative stress tolerance is ambiguous. Here, we characterized the role of FSD1 in response to methyl viologen (MV)-induced oxidative stress in Arabidopsis thaliana. In accordance with the known regulation of FSD1 expression, abundance, and activity, the findings demonstrated that the antioxidant function of FSD1 depends on the availability of Cu2+ in growth media. Arabidopsis fsd1 mutants showed lower capacity to decompose superoxide at low Cu2+ concentrations in the medium. Prolonged exposure to MV led to reduced ascorbate levels and higher protein carbonylation in fsd1 mutants and transgenic plants lacking a plastid FSD1 pool as compared to the wild type. MV induced a rapid increase in FSD1 activity, followed by a decrease after 4 h long exposure. The disruption of FSD1 in fsd1 mutants negatively affected the hydrogen peroxide-decomposing ascorbate peroxidase. Chloroplastic localization of FSD1 is crucial to maintain redox homeostasis. Proteomic analysis showed that the sensitivity of the fsd1 mutants coincided with decrease in abundance of ferredoxin and light photosystem II harvesting complex proteins. These mutants have lower levels of chloroplastic proteases indicating an altered protein turnover in chloroplasts. Remarkably, FSD1 disruption affects the abundance of proteins involved in the defense response. Collectively, the study provides evidence for the conditional antioxidative function of FSD1 and its possible role in signaling.